EKSTERNALITAS EKSPOR ASEAN KE JEPANG DAN AMERIKA SERIKAT - Ady Soejoto; David Kaluge (EKUITAS (Jurnal Ekonomi dan Keuangan), 2005)
The objective of this research is to obtain externalities model of direct export to real GDP several ASEAN states. It is already known thatJapanand United States represent biggest commerce partners to state of ASEAN.From result of analysis, there are significance influences of direct export to Asian Continent andAmericato real GDP some members of ASEAN. Partially, export to Japan andAmericado not fully give  any influence to the real GDP signicance ofMalaysia,Singaporeand of Filippine. Model of Estimation show trend go up for both GDP real and also direct export to the ASEAN country (Indonesia,Malaysia, Philippine, andSingapore).